Driving The Philosophy of Sufficiency Economy into Basic Education Ban Mae O Nai School, Chiang Dao District, Chiang Mai Province - หาจัตุรัส สนิท (Community and Social Development Journal, 2018)
The objective of this qualitative research was to driving the philosophy of sufficiency economy into basic education Ban Mae O Nai School, Chiang Dao District, Chiang Mai Province. The target group consisted of 28 participants. The data were collected by means of a documentary research, an in-depth interview, and a focus group discussion. The content analysis was employed to analyze the data and the findings are presented descriptively. The research results are summarized as follows. The findings reveal that there are three components of the philosophy, namely, sufficiency, logicality, and good immunity, which are based on two conditions: knowledge and ethics. There are two parts of the contents as follows. Part 1: The administration of the basic education institution based on the philosophy. It is composed of five components as follows. 1) Management and administration consist of four components: policy, academics, budget, and general administration. 2) Curriculum development and instructional management consist of four components: learning units on the philosophy, integration of the philosophy into the instruction process, media and learning resources on the philosophy, and learning management measurement and evaluation based on the philosophy. 3) Personnel development consists of three components: student guidance and support system, student affairs, and activities for social development and public utility. 4) Student development activities are composed of two components: personnel development based on the philosophy and follow up as well as further implementation. 5) Outcomes/achievements are composed of four components: institution, school administrators, school personnel, and students. Part 2: A guideline for the implementation of the philosophy into the school should be conducted as follows. 1) Designate educational management policies based on the philosophy as the important school policies. 2) Impart the knowledge about the philosophy in school personnel and board members as well as encourage them to put it into practice and publicize the knowledge about the philosophy to concerned individuals. 3) Revise or improve the administration structure based on the philosophy. 4) Construct, improve or add more projects and activities as well as improve strategic and operation plans of the school. 5) Improve and develop school curricula and conduct classes according to the school curricula. 6) Improve the atmosphere and environment to facilitate efficient learning. 7) Regulate the supervision system, assessment, follow-up, and operation report. 8) Involve parents and community members in educational management in every important step.